Innate Immunity and Influenza A Virus Pathogenesis: Lessons for COVID-19 - Hartshorn, Kevan L. (Frontiers in Cellular and Infection Microbiology, 2020)
There is abundant evidence that the innate immune response to influenza A virus (IAV) is highly complex and plays a key role in protection against IAV induced infection and illness. Unfortunately it also clear that aspects of innate immunity can lead to severe morbidity or mortality from IAV, including inflammatory lung injury, bacterial superinfection, and exacerbation of reactive airways disease. We review broadly the virus and host factors that result in adverse outcomes from IAV and show evidence that inflammatory responses can become damaging even apart from changes in viral replication per se, with special focus on the positive and adverse effects of neutrophils and monocytes. We then evaluate in detail the role of soluble innate inhibitors including surfactant protein D and antimicrobial peptides that have a potential dual capacity for down-regulating viral replication and also inhibiting excessive inflammatory responses and how these innate host factors could possibly be harnessed to treat IAV infection. Where appropriate we draw comparisons and contrasts the SARS-CoV viruses and IAV in an effort to point out where the extensive knowledge existing regarding severe IAV infection could help guide research into severe COVID 19 illness or vice versa.